DETERMINATION OF THE QUANTITY OF VITAMINS CONTAINED IN GRAPES AND THE USE IN FOLK MEDICINE - Askarov I.R; Azimova A.Q; Zhalmurodova D. D; Islamov A.Kh; Zaripova R.Sh (Scholar Express Journals, 2023)
This article provides information on the preparation of molasses from grapes and the determination of its vitamin content, chemical composition and use in medicine
Keywords: grape fruit; grape molasses; vitamins E